Новый вид рода Doloisia (Acariformes, Trombiculidae) с Украины - Гуща, Г.И. (Вестник зоологии, 1983)
Doloisia_(Doloisia) skljari sp. n. is described. The mites were collected from Apodemus sylaticus in the “Khomutovskaya step” State steppe reserve (Donetsk Region, Ukrainian SSR). The new species is closely related to Doloisia synofi Oud emans, 1910; but differs in size. lack of eyes, higher number of the idiosomal setae, presence of the sclerotized platelets on the bases of the setae and other characters, as well as in ecological features. The table is adduced with the differential features of the new species and D. synoti, sensu Oudemans, 1910, 1912; Junker et Brennan, 1962 and KoTebinova, 1979.